Evaluasi Implementasi Sistem Digital Pdam Terhadap Kepuasan Pelanggan Pada Pdam Tirta Manakarra Mamuju - Asfirawati; Yislia; Hari Yeni (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study focuses on evaluating the service performance of PDAM Tirta Manakarra through Importance and Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The IPA analysis classifies service attributes into four quadrants based on their importance and performance levels, highlighting areas requiring improvement or retention. Meanwhile, the CSI assessment reveals an overall customer satisfaction score of 58.22%, indicating "fairly satisfied" status. Recommendations suggest enhancing service quality to achieve higher satisfaction levels. Despite certain attributes meeting satisfactory criteria, continuous improvement efforts are necessary. This study underscores the importance of aligning service delivery with customer expectations, with the potential to elevate PDAM Tirta Manakarra's performance to meet heightened consumer satisfaction standards.